Die Bildungsreflexion Zygmunt Łempickis (1886–1943) zwischen den akademischen Welten in Deutschland und Polen. Inspirationen – Formen – Erbe - Żarski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The aim of the paper is to analyse an ongoing Polish-German project devoted to the Polish philologist Zygmunt Łempicki (1886–1943) and to present the potential, structure, risks and chances of this endeavour involving scholars from Heidelberg, Warsaw and Wroclaw. The Łempicki grant is a work in progress and the author attempts to present how it came to be, starting with the application for the grant, and continuing with the way the cooperation was initiated and the first meetings held, in order to finally present the perspectives for the project’s outcomes. The paper attempts to present its dynamics in order to guarantee a unique insight into the challenges the head of the project meets with. The perspectives for research into the history of German philology in Poland are illustrated and discussed on the example of the specific initiative carried out by means of a cooperation between numerous institutions from different countries.